Correlating Effect Of Polymer Molecular Chain Length And Properties Of Polyvinylidene Difluoride (PVDF) For Carbon Dioxide (CO2) Removal In Membrane Gas Absorption - Baharuddin, Ismat Muhsin (Universiti Sains Malaysia, 2020)
Hydrophobicity of a membrane is one of the main parameters that need to be observed for a membrane to exhibit high efficiency when diffusing gas. The experiment to synthesizing the membrane, characterizing the membrane and performance test on the membrane has been done to compare the ability of Alpha Aeser Polyvinylidene fluoride (PVDF) and Solvex PVDF. Both of the membranes were synthesis by mixing the PVDFs and N-methyl-2-pyrrolidene (NMP) solutions by using the phase inversion method and the coagulation bath used to immerse the membranes was made up of mixture of ethanol and distilled water in the ratio of 20:80. By testing the result using water contact angle test, Alpha Aeser and Solvex membrane exhibit 98.01° and 128.46° respectively. The result shows that the membranes are hydrophobic and superhydrophobic. For the membrane gas absorption (MGA) test, Solvex membrane give better result in separating CO2 gas with monoethanolamine (MEA) compare to Alpha Aeser. After obtaining the all the results and after comparing between both membranes, Solvex membrane was expected to be having lower molecular weight compare to Alpha Aeser because it shows better hydrophobicity and better performance compare to Alpha Aeser.